Retrospective Case Analysis of 104 Cases of Talipes Equinus. (4th October 2022) - Tan, Qian; Yang, Ge; Liu, Yaoxi; Lei, Ting; Ye, Weihua; Hu, Xin; Mei, Haibo
Abstract : A retrospective study of 104 patients (81 male and 23 females, the age range from 2 to 288days) with talipes equinus was conducted to explore the case factors associated with it. We analyzed and discussed the correlation of plaster correction times, age of first visit, gender, and birthplace of patients in the department and understood their correlation and causality. The data were analyzed using frequency analysis, normality test, chi-square goodness-of-fit test, chi-square test, and PLS regression. The findings are set out below. All the distributions of the number of plaster casts in the samples did not have normality. Therefore, we used the nonparametric test and partial least squares regression (PLS regression) and found that the number of plaster casts was more closely related to the age at first visit, gender, and birthplace and had a strong positive correlation. There was a negative correlation between the times of plaster correction and the compliance of braces. The lower the compliance of patients with braces, the more times the plaster correction will be conducted.